2021
DOI: 10.1101/2021.03.22.435873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased ACTL6A Occupancy Within mSWI/SNF Chromatin Remodelers Drives Human Squamous Cell Carcinoma

Abstract: Mammalian SWI/SNF (BAF) chromatin remodelers play dosage-sensitive roles in many human malignancies and neurologic disorders. The gene encoding the BAF subunit, ACTL6A, is amplified at an early stage in the development of squamous cell carcinomas (SCCs), but its oncogenic role remains unclear. Here we demonstrate that ACTL6A overexpression leads to its stoichiometric assembly into BAF complexes and drives its interaction and engagement with specific regulatory regions in the genome. In normal epithelial cells,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…6E), including actin-like 6A (ACTL6A) (Fig. 6F), a subunit of the SWI/SNF chromatin remodeling complex (Chang et al , 2021). Given that LINC00313 modulates chromatin state of certain loci, we investigated the physical and functional association between LINC00313 and ACTL6A deeper.…”
Section: Resultsmentioning
confidence: 99%
“…6E), including actin-like 6A (ACTL6A) (Fig. 6F), a subunit of the SWI/SNF chromatin remodeling complex (Chang et al , 2021). Given that LINC00313 modulates chromatin state of certain loci, we investigated the physical and functional association between LINC00313 and ACTL6A deeper.…”
Section: Resultsmentioning
confidence: 99%
“…Although initial studies of BAF mutations in cancers identified BAF subunits as tumor suppressors, several recent findings suggest that BAF can also function as an oncogene. These include oncogenic fusion of the BAF subunit SS18 with an SSX protein in synovial sarcoma and interaction of BAF with EWS-FLI1 in Ewing sarcoma causing aberrant BAF complex targeting 74,75 , subunit overexpression 76 , and heterozygous missense mutations within the Brg1 subunit gene in diverse cancers, several of which were characterized as gain-of-function for remodeling activity 77 . Furthermore, genetic dependency on Brg1 observed in several cancers has led to the emergence of pharmacological inhibition of the BRG1 ATPase activity as a novel therapeutic strategy 7880 .…”
Section: Discussionmentioning
confidence: 99%
“…The functions of SWI/SNF complexes in squamous cell cancers are ambiguous, as both pro‐tumorigenic and tumour‐suppressive roles have been identified in studies focusing on head and neck SCC 222–224 . A key factor in this puzzle appears to be the SWI/SNF subunit ACTL6A, which, when overexpressed, stoichiometrically assembles into BAF‐type SWI/SNF complexes which then drive chromatin loading of TEAD‐YAP complexes 222 . Should a similar mechanism operate in cSCC, targeting the catalytic subunits of SWI/SNF complexes could be used as therapeutic strategy 225 …”
Section: Targeting Yap and Taz For Skin Cancer Treatmentmentioning
confidence: 99%